Insecticidal activities of the African yam bean seed lectin on the development of the cowpea beetle and the pod sucking bug - Okeola, O.G.; Machuka, J.; Fasidi, I.O. (2002)
The cowpea beetle, Callosobruchus maculatus, and pod-sucking bug, Clavigralla tomentosicollis, are two of the major insect pests of cowpea in Africa. A lectin was purified from the seeds of the African yam bean (AYB), Sphenostylis stenocarpa, by affinity chromatography on Galactosc-Sepharose 4B. The purified AYB lectin (AYBL) was tested on the two insect pests of cowpea. When C. maculatus larvae were fed on artificial cowpea seed containing 0.2, 2, and 5% (w/w) of dietary lectin, larval mortality ranged from 30 to 88% and delay in number of days to first emer gence from 4-13 days. When AYBL was tested on C. tomentosicollis, nymphal mortalities ranged from 76 to 81% at 1% and 87 to 94% at 2%. From 4 to 8%, no nymph survived up to six days after infestation. The results of these insect bioassays provided a scientific basis for isolating a lectin gene from AYB for the transformation of cowpea.